2018
DOI: 10.1371/journal.pone.0201310
|View full text |Cite
|
Sign up to set email alerts
|

Altered hepatic glucose homeostasis in AnxA6-KO mice fed a high-fat diet

Abstract: Annexin A6 (AnxA6) controls cholesterol and membrane transport in endo- and exocytosis, and modulates triglyceride accumulation and storage. In addition, AnxA6 acts as a scaffolding protein for negative regulators of growth factor receptors and their effector pathways in many different cell types. Here we investigated the role of AnxA6 in the regulation of whole body lipid metabolism and insulin-regulated glucose homeostasis. Therefore, wildtype (WT) and AnxA6-knockout (KO) mice were fed a high-fat diet (HFD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 90 publications
2
24
0
1
Order By: Relevance
“…Systemic lipid levels of AnxA6-deficient animals were also comparable to controls after a high fat diet for 17 weeks [61,62]. Most interestingly, AnxA6 KO-mice gained less adipose tissue during high fat feeding [61,62], which might be in line with the impaired proliferation observed in AnxA6-depleted preadipocytes [68]. On the other hand, and in contrast to the cell-based studies described above [68], circulating leptin and adiponectin levels were slightly reduced in high fat diet fed AnxA6 KO-mice [61,62].…”
Section: Annexin Expression Patterns In Adipose Tissue and Their Pmentioning
confidence: 99%
See 3 more Smart Citations
“…Systemic lipid levels of AnxA6-deficient animals were also comparable to controls after a high fat diet for 17 weeks [61,62]. Most interestingly, AnxA6 KO-mice gained less adipose tissue during high fat feeding [61,62], which might be in line with the impaired proliferation observed in AnxA6-depleted preadipocytes [68]. On the other hand, and in contrast to the cell-based studies described above [68], circulating leptin and adiponectin levels were slightly reduced in high fat diet fed AnxA6 KO-mice [61,62].…”
Section: Annexin Expression Patterns In Adipose Tissue and Their Pmentioning
confidence: 99%
“…The plasma membrane and endocytic compartments represent the most common AnxA6 localizations [26,30,63,66,115,116,117,118], but AnxA6 is also found along the secretory pathway [23,25,119], mitochondria [120] and lipid droplets [61,121]. Like other annexins, and depending on the cellular localization and repertoire of interaction partners, AnxA6 participates in many cellular activities, some of which potentially relevant for adipose tissue function, such as endo- and exocytosis, signal transduction, cholesterol homeostasis, stress response [23,25,26,27,30,64,94,116] and lately, neutral lipid accumulation [61,62].…”
Section: Annexin Expression Patterns In Adipose Tissue and Their Pmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies has revealed, that the number of observations suggesting functioning of AnxA6 in exocytosis is limited. Investigators, however, agree that this multifunctional protein plays a regulatory role in membrane trafficking during exocytosis too Cairns et al 2018].…”
Section: Vesicular Transportmentioning
confidence: 99%